Sosialisasi Tentang Penggunaan Media Sosial Dan Konsekuensinya Menurut Hukum Di Negeri Lesluru Kecamatan Teon Nila Serua Kabupaten Maluku Tengah - Panjaitan, Wijaya Natalia; Labetubun, Muchtar Anshary Hamid; Saija, Ronald (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: The utilization of Social Media by the society must be done wisely and be mindful of the legal consequences. Therefore, the society must understand how to use social media properly and keep within the legal rules regulated by the law.Purposes of Devotion: To provide understanding and knowledge to thesociety, especially in providing knowledge of the Importance of using social media wisely and knowing the legal consequences for social media users. Method of Devotion: The devotion method use disthemethod of socialization and facilitation of the Lesluru Village Community.Results of the Devotion: The ability to access information and entertainment offered on social media must be used wisely and understand the legal consequences that exist so that people as social media users can manageand utilize social media according to theirneeds and not violate the rules of applicable law.